CYTOTOXIC ACTIVITY OF ENDOPHYTIC FUNGI HHPCYL03 ISOLATED FROM CYMBOPOGON FLEXUOSUS NEES EX STEUD - Ks, Avinash; L., Krishnamurthy Y. (International Journal of Current Pharmaceutical Research, 2015)
Objective: Cymbopogon grass is one of common aromatic grass species used for extraction of essential oil. The endophytic fungus HHPCYL03isolated from the Cymbopogon flexuosus, a medicinal grass species collected from Kemmannugundi regions of Karnataka. Methods: Secondary metabolites were extracted from fungi using organic solvent Ethyl Acetate and screened for anticancer assay against breast cancer cell (MDA-MB-231), lung cancer cell (Calu-6) and colorectal cancer cell (HCT116) lines. Results: The extract showed the positive result against HCT116 cells. Conclusion: The fungal endophytes certainly become a repository of good economically, socially benefitted bioactive compounds.